The Longest Day - Ryan, Cornelius (Hauppauge, New York : Barron's Educational Series, Inc., 2014)
Reconstructs the events of the Normandy landings from Allied and German reports and eyewitness accounts.
Includes indexes and bibliography.
Keywords: World War, 1939-1945 -- Campaigns -- France -- Normandy; Military campaigns